Everyday irrationality : how pseudo-scientists, lunatics, and the rest of us systematically fail to think rationally /: how pseudo-scientists, lunatics, and the rest of us systematically fail to think rationally. (2018) - Dawes, Robyn M, 1936-2010
No abstract available